Política pública, educación e instrucción pública en los departamentos del Sur de Colombia, 1820-1827 (Estudios) - Soasti Toscano, Guadalupe (2020)
The legal bases of the public school system of the Republic of Colombia in the Distrito del Sur are described. The actions undertaken by the system to enlarge the coverage of schooling and to establish an education structure which ultimately became the basis for Ecuador’s system of education in the nineteenth century are also examined. The drive to promote education was aimed at meeting the regime’s need to build republican civic values by teaching reading and writing skills that would make it possible to disseminate both rights and duties.